Pengaruh Lingkungan Pembelajaran Terhadap Children’s Well-Being Pada Anak Usia Dini - Tsania Mar’atu Sholihah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Children’s well-being is an essential component in supporting optimal development during early childhood, including physical, emotional, social, and psychological dimensions. One of the factors that influences children's well-being in Early Childhood Education (ECE) settings is the quality of the learning environment provided by the institution. This study aims to examine the influence of the learning environment on children's well-being in early childhood through a literature review approach. The research employed a literature review method by analyzing various relevant academic sources, including national and international journal articles, scholarly books, and previous research findings related to learning environments and children's well-being. Data were collected through processes of identification, selection, and critical analysis of literature concerning physical, social, and emotional learning environments in early childhood education settings. The findings indicate that learning environments designed to be safe, comfortable, and supportive of positive interactions between teachers and children contribute significantly to improving children's well-being. A conducive learning environment fosters children's sense of security, happiness, active participation in learning activities, and socio-emotional development. Therefore, effective management of the learning environment is considered an important strategy for educators and early childhood institutions in promoting children's overall well-being